Comparable Disease Severity by Influenza Virus Subtype in the Acute Respiratory Infection Consortium Natural History Study. Issue 7 (26th June 2020) - Schofield, Christina; Colombo, Rhonda E; Richard, Stephanie A; Chen, Wei-Ju; Fairchok, Mary P; Maves, Ryan C; Arnold, John C; Danaher, Patrick J; Deiss, Robert G; Lalani, Tahaniyat; Rajnik, Michael; Millar, Eugene V; et al.
Abstract: Introduction: Since the influenza A/H1N1 pandemic of 2009 to 2010, numerous studies have described the clinical course and outcome of the different subtypes of influenza (A/H1N1, A/H3N2, and B). A recent systematic literature review concluded that there were no appreciable differences in either clinical presentation or disease severity among these subtypes, but study parameters limit the applicability of these results to military populations. We sought to evaluate differences in disease severity among influenza subtypes in a cohort of healthy, primarily outpatient adult U.S. Department of Defense beneficiaries. Materials and Methods: From 2009 to 2014, we enrolled otherwise healthy adults age 18 to 65 years with influenza-like illness in an observational cohort study based in 5 U.S. military medical centers. Serial nasopharyngeal swabs were collected for determination of etiology and viral shedding by polymerase chain reaction. The presence and severity of symptoms was assessed by interview and patient diary. Results: Over a 5-year period, a total of 157 adults with laboratory-confirmed influenza and influenza subtype were enrolled. Of these, 69 (44%) were positive for influenza A(H1N1), 69 (44%) for influenza A(H3N2), and 19 (12%) for influenza B. About 61% were male, 64% were active duty military personnel, and 72% had received influenza vaccine in the past 8 months. Almost 10% were hospitalized with influenza. Seasonal influenza virus distribution among enrollees mirrored that of nationwide trends each year of study. Individuals with A/H1N1 had upper respiratory composite scores that were lower than those with A/H3N2. Multivariate models indicated that individuals with A(H1N1) and B had increased lower respiratory symptom scores when compared to influenza A(H3N2) (A[H1N1]: 1.51 [95% CI 0.47, 2.55]; B: 1.46 [95% CI 0.09, 2.83]), whereas no other differences in symptom severity scores among influenza A(H1N1), influenza A(H3N2), and influenza B infection were observed. Overall, influenza season (maximum in 2012–2013 season) and female sex of the participant were found to be associated with increased influenza symptom severity. Conclusions: Our study of influenza in a cohort of otherwise healthy, outpatient adult Department of Defense beneficiaries over 5 influenza seasons revealed few differences between influenza A(H1N1), influenza A(H3N2), and influenza B infection with respect to self-reported disease severity or clinical outcomes. This study highlights the importance of routine, active, and laboratory-based surveillance to monitor ongoing trends and severity of influenza in various populations to inform prevention measures.